Anaerobic baffled reactor coupled with membrane bioreactor treating tannery wastewater. (May 2022) - Tran, Cong-Sac; Vo, Thi-Kim-Quyen; Dang, Trong B.; Nguyen, Phuong-Thao; Nguyen, Kim-Qui; Hoang, Quang-Huy; Le, Linh-Thy; Nguyen, Thanh-Tin; Bui, Xuan-Thanh
Abstract: Tannery wastewater contains high levels of the organic, inorganic, nitrogenous compound, suspended solids, dissolved solids, and other contaminants (Sulfide, chromium). Anaerobic Baffled Reactor-Membrane Bioreactor (ABR-MBR) system has been introduced as a promising technology for domestic wastewater treatment thanks to its sufficient organic treatment and low energy requirement. This work aimed to evaluate the performance and fouling behavior of the ABR-MBR system for tannery wastewater treatment during 60 d of operation. The ABR system was operated at an organic loading rate (OLR) of 3 kgCOD/m 3 . d while a low flux of 0.75 LMH was retained in the MBR. The results showed that the total COD removal was 89 ± 1% while the NH4 + - N removal ranged from 28 to 33%. The fouling rate of MBR was from 5.14 to 6.18 kPa/d. The fouling degree became severe and this fact could be due to some matters: i) wastewater containing high salinity concentration (around 14, 600 mg/L), ii) operation at high MLSS in MBR (over 10, 000 mg/L), iii) and a short period of aeration time (1–3 min run: 7–9 min relaxation). Overall findings highlighted that the proposed ABR-MBR process could favor minimizing organic matter significantly. Graphical abstract: Image 1 Highlights: Anaerobic Baffled Reactor-Membrane Bioreactor stably remained COD removal (89 ± 1%). Fouling was noticed in MBR, with an increasing rate of 5.14–6.18 kPa/d. Aeration modes (1–3 min run: 7–9 min relaxation) did not favor fouling mitigation.